Familia reconstituida y desarrollo emocional en niños de 7 a 10 años del Recinto San Agustín cantón Babahoyo - Murrieta Ronquillo, Lucia Alexandra (2025)
Reconstituted families involve significant changes in the family structure, relationships, norms and roles, leaving aside everything forged in the previous family. The changes that occur in this type of family can be due to internal or external factors, which can significantly impact the comprehensive development of the infants. The objective of this work is to determine the influence of the reconstituted family on the emotional development of children from 7 to 10 years of age in the San Agustín area of the Babahoyo canton. The methodology implemented was a descriptive, documentary and field research, with a non-experimental design, correlational approach. The methods used were bibliographic, analytical, descriptive and inductive. The population was made up of 156 children from the San Agustín campus of the Babahoyo canton in the period of 2024. The research sample has been determined through non-probabilistic convenience sampling, where 80 children were established. The techniques were a survey and the Koppitz test. The main results showed that the majority of children from 7 to 10 years old have a low to normal level of mental capacity (80-110), which shows that, to a certain extent, there are aspects to improve within the family nucleus of a home. reconstituted.